Analisis Tingkat Kualitas Layanan IT Service Managament Dalam Pelaksanaan Ujian Berbasis CBT Menggunakan Framework ITIL V3 di SMA Negri 1 Sungailiat - Espas, Aldi; Anggraini, Wenny (Fakultas Sains Dan Teknologi Universitas Islam Asyafiiyah, 2025)
This study aims to analyze the quality of IT Service Management services in the implementation of Computer Based Test (CBT) based exams at SMA Negri 1 Sungailiat using the ITIL V3 framework. The research used is qualitative, focusing on the service design domain of ITIL V3, which includes analyzing the availability of IT infrastructure, efficiency and effectiveness of service operations, disruption recovery time, and user satisfaction. The results showed that the CBT system has provided convenience and efficiency in the implementation of the exam, but there are still some obstacles, such as the absence of a formal Service Level Agreement (SLA), decreased performance during mass access, and data security aspects that need to be improved. This research shows that to improve the quality of CBT system services can strengthen IT service management and support the success of the CBT-based Education exam system at SMA Negri 1 Sungailiat.